A comparison of the Hematology Profiles from Preventive and Curative Tests on Lissachatina fulica Snail Mucin Cream for Atopic Dermatitis - Supiyani, Atin; Manalu, Wasmen; Sutardi, Lina Noviyanti; Subangkit, Mawar; Andriyanto, Andriyanto (IPB University, 2025)
Atopic dermatitis (AD) is a chronic inflammatory skin disease. Continuous use of topical NSAIDs in AD cases has been shown to cause adverse effects. Lissachatina fulica mucin (LFM) cream, a natural alternative, has been used for wound healing and can be used as a preventative or curative agent in AD. The objective of this study is to assess the efficacy of LFM cream, exploring its potential as a preventative and curative measure in AD. A total of 36 male BALB/c mice were divided into three cream dosage groups: 0%, 5%, and 10%. The two treatments were preventive and curative, and the two testing times were 0 and 5 days, with three replicates each. Mice were induced with atopic dermatitis by applying 1% DNCB to a 1x1 cm area on their dorsal area for seven days. The preventive group used LFM cream for seven days before DNCB, while the curative group used it after DNCB. Blood samples were collected on days 0 and 5 of the treatment period and analyzed using a hematology analyzer. The data were analyzed using a two-way ANOVA with GraphPad Prism 10, followed by Tukey's test at a 95% confidence level. The toxicity test confirmed that the LFM cream is non-toxic and safe for topical use. The DNCB compound 1% exhibited four main symptoms of atopic dermatitis: pruritus, erythema, excoriation, and lichenification. LFM cream was highly effective, significantly suppressing AD symptoms, with the ADSI score remaining below 2 (p<0.05). Specifically, the curative efficacy was demonstrated by a significant decrease in the ADSI score on day 5 (p<0.05). Hematological analysis revealed statistically significant differences (p<0.05) in the number of lymphocytes, neutrophils, and thrombocytes across groups. The LFM cream is effective and safe for preventative use and successfully treats acute AD at 5% concentration.